2002
DOI: 10.1046/j.1468-3083.2002.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal scleroderma renal crisis caused by gastrointestinal bleeding in a patient with scleroderma, Sjögren's syndrome and primary biliary cirrhosis overlap

Abstract: A 57-year-old female patient presented with a long history of overlapping autoimmune disease, including limited cutaneous systemic sclerosis, Sjögren's syndrome and primary biliary cirrhosis. Another unusual finding was that the mild skin involvement (limited cutaneous systemic sclerosis, subcutaneous calcinosis) was combined with serious internal organ involvement, including honeycombing and finally scleroderma renal crisis. The most important finding was, that two decades later she developed severe telangiec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 26 publications
3
20
1
Order By: Relevance
“…Interestingly, we observed that watermelon stomach was an early manifestation in SSc, as it more often occurred in earlier phase of the disease (<5 years after SSc diagnosis). Moreover, progression of watermelon stomach and activity of SSc have rarely been reported previously; the manifestations of watermelon stomach and the activity of SSc did not seem to parallel each other (62.5%) 18–40 . Our findings underline that both watermelon stomach and SSc progressed simultaneously in only 33.3% of patients; in other patients, watermelon stomach occurred when other manifestations of SSc were quiescent.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Interestingly, we observed that watermelon stomach was an early manifestation in SSc, as it more often occurred in earlier phase of the disease (<5 years after SSc diagnosis). Moreover, progression of watermelon stomach and activity of SSc have rarely been reported previously; the manifestations of watermelon stomach and the activity of SSc did not seem to parallel each other (62.5%) 18–40 . Our findings underline that both watermelon stomach and SSc progressed simultaneously in only 33.3% of patients; in other patients, watermelon stomach occurred when other manifestations of SSc were quiescent.…”
Section: Discussioncontrasting
confidence: 44%
“…Various clinical presentations may reveal watermelon stomach. In the literature analysis of 77 SSc patients, the initial presentation of watermelon stomach was more commonly recurrent anaemia related to occult gastrointestinal bleeding (90.9% of cases) 18–40 . In our experience, we found that 86.7% of patients presented with iron‐deficiency anaemia.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…3 Several studies of limited cutaneous scleroderma have described that renal crisis occurred in the patients who had such autoantibodies as anti-RNA polymerase III antibody, anti-Th/To antibodies, or anti-U1/ U3 RNP antibodies. [8][9][10][11][12][13] Katrib et al have reported three patients with anticentromere antibody-positive limited cutaneous systemic sclerosis who developed renal failure, but these patients showed normal blood pressure, active urinary sediments, positive antineutrophil cytoplasmic antibodies, and crescentic glomerulonephritis, 12 indicating that these cases were not classical scleroderma renal crisis. A case has been reported of a patient with scleroderma and primary biliary cirrhosis overlap who had fatal scleroderma renal crisis, but she had massive gastrointestinal bleeding and had no anticentromere antibody, 13 suggesting that this case was also not typical scleroderma renal crisis.…”
Section: Discussionmentioning
confidence: 99%